Disentangling the life-cycles of Bronze Age pits: a multi-stranded approach, integrating ceramic refitting, archaeobotany and taphonomy - Martín-Seijo, María (2017)
Pits are the most common archaeological features in late prehistoric Europe, yet their function and formation dynamics remain obscure. This paper draws on stratigraphy, contextual observations, and a novel analytical protocol to address such topics. The article presents an interdisciplinary and comparative post-excavation procedure to evaluate some of the most abundant items found in prehistoric pits, combining a taphonomical approach to the analysis of ceramics, charcoal, and carpology. This procedure provided new insights into the use-lives of a selection of five pits from an open-air site in Galicia (NW Iberia), which was occupied intermittently during the second millennium cal. BCE. An early use as silos is posited, and their final closure entailed cultural practices and preferences whose material fingerprint has been identified via multivariate analysis.